2022
DOI: 10.1002/ange.202200206
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Electrothermal Flow‐Enhanced Magneto Biosensor for Highly Sensitive Protein Detection in Whole Blood

Abstract: Current diagnostic tests for sensitive protein detection rely on immunological techniques, such as ELISA, which require sample purification, multiple washing steps and lengthy incubation, hindering their use for rapid testing. Here, we report a simple electrothermal flow-enhanced biosensor for ultrafast, high sensitivity measurements of protein biomarkers in whole blood. Magnetic nanobeads dually-labeled with a detection antibody and enzyme reporter are used to form immunocomplexes with the target protein, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In this work, the immunorecognition process was performed in an Eppendorf tube to avoid interference with the electrode interface. Additionally, PEGylated immunomagnetic beads formed a hydrated layer on the surface to resist the adhesion of nonspecific proteins. , Typically, routine immunorecognition processes demand a lengthy incubation period (>2 h), resulting in slow detection. Therefore, a vortex mixer was employed to assist this process and dramatically accelerated the kinetics of movement and binding between antibodies and antigens. By optimizing the incubation time between antigens and the immunoprobe, the sandwich-structure of immunocomplex (Fe 3 O 4 /Ab 1 /PEG@antigen@SiO 2 /Ab 2 /3-ABA) was formed within 10 min.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, the immunorecognition process was performed in an Eppendorf tube to avoid interference with the electrode interface. Additionally, PEGylated immunomagnetic beads formed a hydrated layer on the surface to resist the adhesion of nonspecific proteins. , Typically, routine immunorecognition processes demand a lengthy incubation period (>2 h), resulting in slow detection. Therefore, a vortex mixer was employed to assist this process and dramatically accelerated the kinetics of movement and binding between antibodies and antigens. By optimizing the incubation time between antigens and the immunoprobe, the sandwich-structure of immunocomplex (Fe 3 O 4 /Ab 1 /PEG@antigen@SiO 2 /Ab 2 /3-ABA) was formed within 10 min.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to bacteria detection, dually labeled magnetic nanoparticles have recently been applied for virus detection [1,62]. Li and Lillehoj [64] developed an alternating current electrothermal flow (ACEF)-enhanced magneto-immunosensor to detect Plasmodium falciparum histidine-rich protein 2 (Pf HRP2). They synthesized dually labeled MNPs (carboxylated magnetic nanobeads, diameter: 200 nm) which were conjugated with HRP and HRP-conjugated anti-Pf HRP2 IgG antibodies at 200:1 molar ratio.…”
Section: Mnps-antibody-hrp Coating Methodsmentioning
confidence: 99%
“…For this consideration, Premaratne et al demonstrated that the adsorption of MBs on the electrode through the antibody–antigen interaction could increase the resistance to the redox probe in solution [ 186 ]. Enzymes and antibodies can be simultaneously immobilized on the MBs for pre-concentration of target and signal readout [ 187 , 188 ]. Sadasivam et al reported a magnetically assisted electrochemical detection of the carbohydrate antigen CA125 with enzyme- and antibody-modified MBs [ 189 ].…”
Section: Mb/mnp-based Target Conversionmentioning
confidence: 99%